Analisis Sumber dan Jenis Pembiayaan Pendidikan di Indonesia - Nadhifa Ardiana Maharani; Fitri Hidayah; Diki Darmawan; Syunu Trihantoyo (Pusat Riset dan Inovasi Nasional, 2024)
This research uses a systematic literature review method with the PRISMA model to examine the sources and types of education financing in Indonesia. Data was obtained through a literature study, by analysing 25 journal articles from 2013-2023 that were relevant to the subject matter. Of the 25 articles, 12 were identified as relevant, which were then re-analysed. The results of the analysis showed that there were 10 articles that discussed the sources and types of education financing in Indonesia with a focus on the efficiency of education fund management, while 2 articles were considered less relevant because they talked about the basic concepts of financing and financing planning. The discussion in this study is about the definition and concept of education financing, legal basis, types of financing, and sources of financing such as government funds, community donations, and parental contributions. The education financing cycle includes planning, accounting and evaluation to ensure the effective and efficient use of financial resources. This research provides an in-depth understanding of education financing in Indonesia, highlighting the important roles of government, communities and educational institutions in providing funds to support the sustainability and quality of education